Individual inquiry as a pertinent philosophical putting in question - Huang, Rosângela (O Mundo da Saúde, 2012)
The first part of this article brings segments of an interview given by D., born in Argentina in 1957, the son of Polish father and a Hungarian mother. His parents had run away from Nazi persecution to Jews in Europe during World War II. In Argentina, persecution compelled them to run away again, this time to Israel. In 1960 they arrived to Brazil. The second part of the article analyzes how freedom searching by this family produced deep suffer5ngs and losses to D., which began to construct a unique perspective on the world and himself. D. was chosen for this interview due to the force with he said “no” to so many situations where most of us are compelled to say “yes”. D. is a free thinker, a spiritualist and musician, a self-taught person who says with boldness: “Life was given me, but death is my choice.” The aim of this article is to show the importance of allowing others to speak and be listened. To give voice to others is a type of acceptance, a meditation in which one rescues senses, in which history survives and alleviates pain of sufferings through acceptance and understanding of possible transformation, the one that is up to everyone before the unusual, to undesired. The paper register one of those moments of listening which an interview allows to happen and is part of a work presented in the undergraduate course in Psychology of Centro Universitário São Camilo in October 2011.